Extracranial Carotid and Vertebral Artery Disease Contemporary Management (Springer International Publishing, 2018)
Carotid and vertebral artery disease affects a large segment of the population with the potential of causing severe disability from a major stroke. This book places emphasis on the medical, endovascular and surgical approaches in managing patients with extracranial carotid and vertebral artery disease following pertinent diagnostic studies. Sections focus on carotid and vertebral anatomy, physiology and diagnostic modalities. Subsequent chapters discuss specific disease processes and their management with the best medical therapy neuro-interventions. Contributions from many interrelated specialties, including cerebrovascular physiology, pathology, neuro-radiology, neuro-interventions, stroke-neurology and vascular surgery significantly enhance our knowledge of carotid and vertebral artery disease. Extracranial Carotid and Vertebral Artery Disease: Contemporary Management provides an comprehensive and state-of-the-art approach to managing complex arterial reconstructions. .